The two types of El‐Niño and their impacts on the length of day. Issue 10 (20th May 2014) - de Viron, O.; Dickey, J. O.
Abstract At the interannual to decadal time scale, the changes in the Earth rotation rate are linked with the El‐Niño–Southern Oscillation phenomena through changes in the atmospheric angular momentum. As climatic studies demonstrate that there were two types of El‐Niño events, namely, eastern Pacific (EP) and central Pacific (CP) events, we investigate how each of them affects the atmospheric angular momentum. We show in particular that EP events are associated with stronger variations of the atmospheric angular momentum and length of day. We explain this difference by the stronger pressure gradient over the major mountain ranges, due to a stronger and more efficiently localized pressure dipole over the Pacific Ocean in the case of EP events.